(untitled) (Quest Journal of Management and Social Sciences, 2024)
Background: Interest rate fluctuations have long been a critical research topic, particularly in relation to retail loan holders. In Nepal, the status of retail loans has been progressively improving, making it essential to understand how interest rate changes affect retail loan borrowers in Kathmandu Valley. Objective: This study aims to investigate the impact of interest rate fluctuations on retail loan holders in Kathmandu Valley. It seeks to determine how these fluctuations influence banking performance and retail loan products in the context of Nepalese financial institutions. Method: A descriptive research design was employed, focusing on retail loan holders from Nepalese financial institutions in Kathmandu Valley. A sample of 383 retail loan borrowers was selected using simple random sampling. Data were collected via a structured questionnaire. The analysis involved descriptive statistics, correlation, regression, as well as pre-estimation and post-estimation techniques. Result: The findings indicate that interest rate fluctuations have a positive and significant impact on retail loan products offered by Nepalese banking institutions. Higher interest rates tend to enhance retail loan offerings, contributing to improved banking performance and increased creativity in loan practices. Conclusion: The study underscores the positive role of interest rate fluctuations in shaping retail loan products and banking performance in Nepal. It suggests that financial institutions could benefit from adjusting their interest rates to foster better loan practices and improve overall performance. For economic benefit, banks should consider lowering interest rates and providing attractive returns to depositors to balance their profitability and enhance financial stability. This research provides a foundation for further academic exploration into the effects of interest rates on retail loan behavior. Paper Types: Research Paper Keywords: Interest rate, Retail banking products, Ordered logistic model, Kathmandu valley. JEL Classification: G1, E43, G21 and G41